Current Status, Hot Topics, and Trends in Green Certificate Research: A Bibliometric Analysis Based on WoS Data - Chen, Yingying; Ma, Xiaojie; Zhu, Wenlong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
Green certificates are pivotal in sustainable energy governance amid global climate action. This study addresses gaps in systematic bibliometric analysis of their evolution, analyzing 459 Web of Science articles (2001–2024) via R bibliometrix across six dimensions. Four novel and valuable findings are identified. First, global scholarly interest in green certificates demonstrates sustained annual growth, with notable acceleration post-2021 when research output peaked. Second, China, the USA, and Sweden constitute the primary research contributors, collectively producing 187 documents. Third, contemporary green certificate research predominantly features solitary authorship or limited-scale collaborations. Fourth, contemporary focal points in green certificate research concentrate on policy design, system optimization for power grids, market mechanism innovation, and operational efficiency analysis of certification systems. Findings advance understanding of green certificate dynamics, offering strategic insights for optimizing policy design, market integration, and renewable energy transitions.